A metal hydride air-conditioning system for fuel cell vehicles – Functional demonstration. (1st February 2020) - Weckerle, C.; Nasri, M.; Hegner, R.; Bürger, I.; Linder, M.
Highlights: System uses potential energy in H2 pressure tank for A/C effect by metal hydrides. Alternately operating metal hydride reactors integrated between tank and PEM FC. First experimental demonstration with 2 × 1.5 kg metal hydride. Spec. cooling power of 227 W kgMH −1 reached at an electrical power of 5 kWel . Abstract: High pressure storage of hydrogen is the established storage technology for automotive systems. However, around 15% of the lower heating value of hydrogen is spent to compress hydrogen up to the pressure of 700 bar. Since this energy is available on board but so far wasted, an open air-conditioning system based on metal hydrides is promising to reutilize this compression work. Here we present the experimental demonstration of a first of its kind system. The setup consists of two alternately operating plate reactors, each filled with around 1.5 kg of Hydralloy C2 ( T i 0.98 Z r 0.02 V 0.41 F e 0.09 C r 0.05 M n 1.46 ), coupled to a polymer electrolyte membrane fuel cell. The demonstration at an electrical power of 5 kW shows that the fuel cell operation is not affected by the alternately H2 desorbing reactors (half-cycle duration of 150 s). The system's average cooling power was 662 W for an ambient temperature of 30 °C and a cooling temperature of 20 °C, reaching of specific cooling power of 227 W k g M H - 1 . Related to the maximum obtainable cooling power of 18.3% of the electrical fuel cell power, the cooling efficiency corresponds to 75%. As an innovative hydrogen pressure transducer the presented system can be transferred to all applications where an unused hydrogen pressure difference is available.